2019
DOI: 10.28991/cej-2019-03091366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sheet Pile Driving on Geotechnical Behavior of Adjacent Building in Sand: Numerical Study

Abstract: Construction vibration such as sheet pile driving can produce earthborn vibrations which may be leads to problems for the supporting soils and adjacent structures. Vibrations create the stress waves traveling outward from the source through the soil and cause structural damage due to dynamic vibration induced settlement. The main aim of the present research is to study the vibration effect through sheet pile driving technique on the surrounding soil and adjacent structure. A series of plain strain finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hytham et al also studied the effect of SSI on steel frame structure with and without infill wall and further extended this to study the effect of pounding [24]. Basha et al found out the best position of the belt truss system and out trigger including SSI [25]. Nishant et al investigated the importance of including SSI in design codes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hytham et al also studied the effect of SSI on steel frame structure with and without infill wall and further extended this to study the effect of pounding [24]. Basha et al found out the best position of the belt truss system and out trigger including SSI [25]. Nishant et al investigated the importance of including SSI in design codes [26].…”
Section: Introductionmentioning
confidence: 99%
“…The design of sheet piling can be carried out with the use of precise methods taking into account the adopted model of the ground substrate, using MES modelling and appropriate computer programs [8,9]. It is also possible to use analytical methods known from general mechanics solutions depending on the adopted static diagram or approximate graphic and analytical methods such as Blum's method [10,11].…”
Section: Analysis Of the Calculation Methods For Sheet Pilingmentioning
confidence: 99%
“…According to Jones and Holtz [1], the damages in light weight buildings and roads caused by expansive soils attained to $2.2 billion in USA only. At bottom tip of pile, pore water pressure is increased due to vibration source [2]. In South Africa over (R100 million) is spent on affecting remedial works on buildings on expansive soils [3].…”
Section: Introductionmentioning
confidence: 99%